A first-in-class, non-invasive, immunodynamic biomarker approach for precision immuno-oncology. (31st December 2022) - Sprooten, Jenny; Coosemans, An; Garg, Abhishek D.
ABSTRACT: Non-invasive, immuno-dynamic, biomarkers positioned in cancer patient's blood milieu with immuno-oncological applications are rare. We recently established a "first-in-class" serum functional immunodynamics status (sFIS) assay, wherein in vitro assessment of serum-induced myeloid NFkB and/or interferon (IFN) response-signaling can be performed to "mimic" in situ patient's serum immune-biology. This modality has clear implications for anticipating patient prognosis and immunotherapy-relevant stratification.